EDUKASI GIZI DAN TUMBUH KEMBANG ANAK SERTA PEMBERIAN MAKANAN TAMBAHAN (PMT) PADA IBU RUMAH TANGGA DI DESA KUDU BAKI SUKOHARJO - Noor Izra Firmansyah; Furqon Mahendra; Khansa Ulfiya Nu'ma Emarin; Nimas Zuhrufana; Shafira Eka Damayanti; Fihlia Hardiyantika; Fiana Rosalia Putri; Diana Dwika Puspitasari; Vivin Dwi Febriyanti; Haniifah Husni Zaa'idah; Mahatma Dewi; Nurlita Buana Jati; Ekan Faozi; Diah Pebriani; Dwi Astuti (Universitas Muhammadiyah Surakarta, 2025)
Stunting is a chronic nutritional problem that is still often found in Indonesia, including in Kudu Village, Baki Subdistrict, Sukoharjo District. One of the causes is the low knowledge of mothers regarding nutritional needs and stimulation of child growth and development. This community service activity aims to increase the knowledge of mothers of toddlers about balanced nutrition and child development through health counseling and demonstration of making Supplementary Feeding (PMT). The activity used a one group pre-test post-test design and involved 17 mothers of toddlers. The intervention was conducted through counseling and demonstrative practice of making PMT. Evaluation was conducted using a toddler nutrition knowledge questionnaire and PMT processing. Results showed significant improvements in nutrition knowledge scores (from 76.96 to 88.24; p=0.001) and PMT processing knowledge (from 74.02 to 87.26; p=0.000). It can be concluded that this educational approach is effective in improving mothers' knowledge and has the potential to support stunting prevention efforts at the community level. To maintain the sustainability of the program, it is recommended that this activity be part of the routine agenda of the Posyandu.